1994
DOI: 10.1172/jci117218
|View full text |Cite
|
Sign up to set email alerts
|

Secretion-recapture process of apolipoprotein E in hepatic uptake of chylomicron remnants in transgenic mice.

Abstract: To investigate the role of apoE in hepatic uptake of chylomicron remnants, we studied chylomicron metabolism in transgenic mice overexpressing apoE in the liver. Plasma clearance of injected "25I-labeled human chylomicrons was fivefold faster in transgenic mice than in controls. Immunohistochemistry demonstrated that apoE was specifically localized at the basolateral surface of hepatocytes from fasted transgenic mice. After injection ofa large amount of chylomicrons, the density of the cell surface apoE was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…1, was excised after agarose-electrophoresis, purified by extraction with phenol and chloroform, and used for microinjection. Transgenic mice was produced as previously described (12) embedded sections of the materials were subjected to immunohistochemistry as previously described (25). The primary antibodies used were a goat anti-human apoE antibody at 1:200.…”
Section: Methodsmentioning
confidence: 99%
“…1, was excised after agarose-electrophoresis, purified by extraction with phenol and chloroform, and used for microinjection. Transgenic mice was produced as previously described (12) embedded sections of the materials were subjected to immunohistochemistry as previously described (25). The primary antibodies used were a goat anti-human apoE antibody at 1:200.…”
Section: Methodsmentioning
confidence: 99%
“…infusion of apoE in cholesterol-fed rabbits and the demonstration of accelerated clearance of β-VLDL remnants from the blood and their uptake by the liver (10). In transgenic mice and rabbits, overexpression of apoE accelerated remnant clearance (11)(12)(13). Furthermore, apoE was localized to the sinusoids in the space of Disse, and after infusion of remnant lipoproteins, apoE disappeared from the sinusoids and appeared in hepatocytes (14).…”
Section: Role Of Apoe In Remnant Binding and Uptakementioning
confidence: 99%
“…Local hepatic expression of apo E has been proposed to promote receptor-mediated endocytosis by the LRP (20) or by both the LDLR and the LRP (14,18). Shimano et al reported that after the injection of human chylomicrons into transgenic mice overexpressing rat apo E in the liver, the density of apo E staining by immunocytochemistry at the basolateral surface of the hepatocyte decreased and there was an increase in vesicular staining in the cytoplasm, suggesting that apo E on the cell surface was used for the endocytosis of chylomicron remnants (21). However, definitive proof of the existence of the secretion-capture mechanism and demonstration of its physiologic relevance in vivo have been lacking.…”
Section: Introductionmentioning
confidence: 99%